A Review of Studies with Chlorhexidine Applied Directly to the Umbilical Cord (American Journal of Perinatology, 2013)
Infection-related neonatal mortality due to omphalitis in developing country home births is an important public health problem. Three cluster randomized trials of 4% chlorhexidine applied to the umbilical cord stump from once to multiple times in the days following a home birth have evaluated this intervention compared with other types of cord care on the development of omphalitis and neonatal mortality. Each of the three studies showed significant reductions in either omphalitis, neonatal mortality, or both with the 4% chlorhexidine. However, the optimal dosing schedule remains uncertain. Although further studies are needed to clarify this issue, from the three studies it is now clear that with a minimum of one application of 4% chlorhexidine to the umbilical cord stump following delivery, the incidence of omphalitis and neonatal mortality can be reduced, especially in preterm newborns. This intervention, which is safe and inexpensive and requires minimal training and skill, should strongly be considered for adoption wherever home births occur.
Keywords: chlorhexidine; neonatal mortality; cord care; developing countries